مؤشرات الاستقرار السياسي في الكويت في الفترة من 2010 وحتى 2019 - العجمي، هادي عايض (جامعة حلوان - كلية التجارة وإدارة الاعمال, 2020)
تعتبر الكويت من الدول الحديثة، والآخذة في النمو، ومن بين الدول التي استقرت مؤسساتها السياسية إلى حد كبير وتطورت بشكل صحي مما جعلها تمتلك مجلس أمة يتمتع بصلاحيات واسعة، ومشاركة شعبية كبيرة لذلك له دور كبير في الحياة السياسية الكويتية. ويرجع ذلك بالأساس إلى أن دولة الكويت قامت على أساس عقد اجتماعي بين أسرة آلصباح والشعب الكويتي، وقد استمر هذا العقد حتى بعد استقلال الكويت، حيث نشأت لدى النخبة الحاكمة قناعة تامة بأن وجود دستور وطني ومجلس تشريعي منتخب من الشعب هما الضمانة الأمثل لقيام دولة ديمقراطية دستورية حديثة توازن بين شرعية الحكم الذي تتمتع بها الأسرة الحاكمة، والمشاركة السياسية للشعب في إدارة البلاد وذلك من خلال مجلس الأمة الذي يعبر عن إرادة الشعب ومشاركته في صنع القرار السياسي، وكل ذلك يصب بشكل كبير في جانب الاستقرار السياسي للدولة خصوصا ما يتعلق بديمقراطية النظام والقيادة والشرعية وعلاقات النظام الداخلية والخارجية. إلا أن الصراع المستمر بين السلطتين التشريعية والتنفيذية أثر بشكل كبير على الاستقرار السياسي للكويت في الفترة محل الدراسة وهو ما انعكس على عدم استقرار المناصب السياسية سواء الحكومة أو دورات البرلمان.
Kuwait is one of the modern and growing countries, and among the countries whose political institutions have largely stabilized and developed in a healthy manner, which makes them possess a parliament with wide powers, and a large popular participation for that has a great role in Kuwaiti political life. This is mainly due to the fact that the State of Kuwait was established on the basis of a social contract between the Al-Sabah family and the Kuwaiti people, and this contract continued even after the independence of Kuwait, where the ruling elite developed a complete conviction that the existence of a national constitution and an elected legislative council from the people are the best guarantees for the establishment of a democratic state A modern constitutional balance between the legitimacy of the rule enjoyed by the ruling family, and the political participation of the people in the management of the country, through the National Assembly, which expresses the will of the people and their participation in political decision-making, and all of this is largely in the aspect of the political stability of the state, especially with regard to the democracy of the system and leadership Legitimacy and internal and external system relationships. However, the ongoing conflict between the legislative and executive branches greatly affected the political stability of Kut in the period under study, which reflects a reflection on the instability of political positions, whether government or parliament sessions.
Keywords: الكويت -- النظام السياسي -- الاستقرار السياسي -- المعارضة السياسية -- المؤشرات السياسية